Impact of Macroeconomic Variables on Stock Market of Malaysia - Rasheed, Alam; Saeedi, Mitra; Gebril, Nalini; Hariraj, Kumaraseh (International Journal of Psychosocial Rehabilitation, 2020)
This research examines the long-run and short-run relationship between selected macroeconomic variables (interest rate, inflation, money supply, and world oil price and exchange rate) and the stock market of Malaysia using monthly data from 2002 to 2015. The mobilization of funds into useful economic activity increases productivity, which has a great impact on the economics of a country. The research applies the autoregressive distributed lags (ARDL) model to examine long-run and short-run relationships. The results reveal that stock prices in Malaysia have a long-term relationship with the selected macroeconomic variables; however, the short-run relationship is found to be weak. These findings provide insights for investors and analysts to consider these factors in portfolio selection. This research also gives policy direction to the government in the implementation of monetary policy.